How metaverse music platform cues shape content creation behavior: Evidence from social and flow pathways - Qiyue Song; Di Mu; Xiaodi Peng; Guanzhou Liu (PLoS ONE, 2026)
This study examines how metaverse music platform design influences users’ content creation behavior. Drawing on the Stimulus–Organism–Response framework, it develops a dual-path model in which relational-affective cues shape social experience, whereas interaction-oriented cues shape flow experience. Both experiential states are proposed to enhance emotional value perception, which in turn predicts content creation behavior, with technology acceptance examined as a boundary condition. Results from a survey of 435 Chinese users of metaverse music platforms show that emotional resonance and social presence positively predict social experience, whereas aesthetic novelty does not. Avatar customization, narrativity, and multi-sensory positively predict flow experience. Social experience and flow experience both strengthen emotional value perception, which subsequently increases content creation behavior. Technology acceptance strengthens only the social experience route. The study contributes by extending SOR research to metaverse music platforms, clarifying that music-related posting and sharing is shaped through distinct social and flow-based pathways, and showing that technology-related beliefs function as a selective boundary condition rather than a uniform amplifier across the model.